Detection of the presence and distribution of invasive fish in the Progo River, Yogyakarta, Indonesia using the environmental DNA method - Kurnia Anggraini Rahmi; Ratih Ida Adharini; Dini Wahyu Kartika Sari; Tony Budi Satriyo (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rahmi KA, Adharini RI, Sari DWK, Satriyo TB. 2023. Detection of the presence and distribution of invasive fish in the Progo River, Yogyakarta, Indonesia using the environmental DNA method. Biodiversitas 24: 276-281. Invasive species are alien species that enter the ecosystem and can adapt to the ecosystem quickly. So, the presence of invasive fish can threaten endemic diversity in these ecosystems. This study aims to detect the presence and distribution of invasive fish in the Progo River, Yogyakarta, Indonesia, through the environmental DNA (eDNA) method. Water samples were taken at three observation points in the upstream area of the river (site 1), the middle of the river (site 2), and downstream of the river (site 3). The water samples were filtered using 0.45 µm MF-Milipore installed on the filtration pump and extracted using the ZymoBIOMICS DNA Miniprep Kit. Sequencing used nanopore sequencing. The primers used were FishF2 and FishR2. The sequencing results were analyzed using the mBRAVE software, which was then classified as an invasive species based on government regulations and journals. The results showed that 188 OTUs were detected in the upstream area (site 1), 227 OTUs in the middle area (site 2) and 154 OTUs downstream. Lagocephalus and Sciaenops were found in the upstream area (site 1). In the middle area of the river (site 2), Gambusia and Lepomis were found, while in the lower reaches of the river (site 3), Gambusia and Sciaenops were found. With the detection of these invasive species, appropriate management and conservation efforts must be carried out immediately to protect endemic species in the Progo River.